Perubahan Makna Simbolik Batu Nisan Aceh Pasca Kolonial: Kajian Semiotika Budaya - Iskandar Iskandar; Yulfa Haris Saputra; Amris Albayan (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study examines the shift in the symbolic meaning of Acehnese gravestones in the postcolonial context. Although their visual forms have largely remained unchanged, the community’s interpretation of the symbols carved upon them has shifted significantly. Symbols that once embodied religious and social values are now often reinterpreted merely as aesthetic ornaments. Using Charles Sanders Peirce’s cultural semiotic approach, this research analyzes how the same signs are read differently by societies over time. Field observations, visual documentation, and in-depth interviews with local cultural figures and historians were conducted. The findings reveal a paradigm shift from a transcendent worldview to a materialistic-aesthetic one, where meaning is seen as inherent in material form. This study contributes to a deeper understanding of how material cultural symbols are reinterpreted within Acehnese modernity.